A remote nonconjugated electron effect in insertion polymerization with α-diimine nickel and palladium species. Issue 15 (20th March 2020) - Li, Shuaikang; Xu, Guoyong; Dai, Shengyu
Abstract : The remote nonconjugated electronic perturbations exert great influence on ethylene polymerization. Abstract : Systematic investigations of ligand electronic effects in late transition metal catalyzed ethylene polymerization and copolymerization have been widely explored in different catalytic systems. Generally, the electronic effect regulation in olefin polymerization can be achieved by replacing substituents with different electronic effects through the conjugate effect to influence the catalytic metal center. In this contribution, we describe the synthesis and characterization of a series of bulky α-diimine ligands and the corresponding nickel and palladium catalysts bearing a diarylmethyl moiety with different electronic effects. The bulky nickel complexes show great thermal stability, and achieve the highest activity at 80 °C in ethylene polymerization. The generated polyethylene possesses very high molecular weight, moderate branching density and moderate melting temperature even at 80 °C. The corresponding palladium complexes display moderate activity and generate high molecular weight semicrystalline polyethylene with low branching density. The high molecular weight polar functionalized polyethylene can also be obtained using these palladium complexes. Surprisingly, the remote nonconjugated electronic perturbations exert great influence on the ethylene polymerization in terms of the polymerization activities and polymer microstructures.